The cost of mental disorders: a systematic review. (2020) - Christensen, M. K.; Lim, C. C. W.; Saha, S.; Plana-Ripoll, O.; Cannon, D.; Presley, F.; Weye, N.; Momen, N. C.; Whiteford, H. A.; Iburg, K. M.; McGrath, J. J.
Abstract: Aims: To identify and synthesise the literature on the cost of mental disorders. Methods: Systematic literature searches were conducted in the databases PubMed, EMBASE, Web of Science, EconLit, NHS York Database and PsychInfo using key terms for cost and mental disorders. Searches were restricted to January 1980–May 2019. The inclusion criteria were: (1) cost-of-illness studies or cost-analyses; (2) diagnosis of at least one mental disorder; (3) study population based on the general population; (4) outcome in monetary units. The systematic review was preregistered on PROSPERO (ID: CRD42019127783). Results: In total, 13 579 potential titles and abstracts were screened and 439 full-text articles were evaluated by two independent reviewers. Of these, 112 articles were included from the systematic searches and 31 additional articles from snowball searching, resulting in 143 included articles. Data were available from 48 countries and categorised according to nine mental disorder groups. The quality of the studies varied widely and there was a lack of studies from low- and middle-income countries and for certain types of mental disorders (e.g. intellectual disabilities and eating disorders). Our study showed that certain groups of mental disorders are more costly than others and that these rankings are relatively stable between countries. An interactive data visualisation site can be found here: https://nbepi.com/econ . Conclusions: This is the first study to provide a comprehensive overview of the cost of mental disorders worldwide.